All the pups we cannot see: Cannibalism masks perinatal death in laboratory mouse breeding but infanticide is rare
Perinatal mortality is a major issue in laboratory mouse breeding. We compared a counting method using daily checks (DAILY_CHECK) with a method combining daily checks with detailed video analyses to detect cannibalisms (VIDEO_TRACK) for estimating the number of C57BL/6 pups that were born, that died and that were weaned in 193 litters from trios with (TRIOOVERLAP) or without (TRIO-NO_OVERLAP) the presence of another litter. Linear mixed models were used at litter level. To understand whether cannibalism was associated with active killing (infanticide), we analysed VIDEO_TRACK recordings of 109 litters from TRIO-OVERLAP, TRIONO_OVERLAP or SOLO (single dams). We used Kaplan-Meier method and logistic regression at pup level. For DAILY_CHECK, the mean litter size was 35% smaller than for VIDEO_TRACK (p < 0.0001) and the number of dead pups was twice lower (p < 0.0001). The risk of pup loss was higher for TRIO-OVERLAP than TRIO-NO_OVERLAP (p < 0.0001). A high number of pup losses occurred between birth and the first cage check. Analyses of VIDEO_TRACK data indicated that pups were clearly dead at the start of most of the cannibalism events and infanticide was rare. As most pups die and disappear before the first cage check, many breeding facilities are likely to be unaware of their real rates of mouse pup mortality.